2017
DOI: 10.1103/physrevlett.119.156802
|View full text |Cite
|
Sign up to set email alerts
|

Hole Spin Resonance and Spin-Orbit Coupling in a Silicon Metal-Oxide-Semiconductor Field-Effect Transistor

Abstract: We study hole spin resonance in a p-channel silicon metal-oxide-semiconductor field-effect transistor. In the sub-threshold region, the measured source-drain current reveals a double dot in the channel. The observed spin resonance spectra agree with a model of strongly coupled two-spin states in the presence of a spin-orbit-induced anti-crossing. Detailed spectroscopy at the anticrossing shows a suppressed spin resonance signal due to spin-orbit-induced quantum state mixing. This suppression is also observed f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 50 publications
3
57
0
Order By: Relevance
“…The current confirms the presence of appreciable spin orbit interaction (SOI) whose strength is controlled by the applied voltage to a gate electrode. Similar magneto-conductance measurements through a double dot formed in the channel of a silicon transistor device have demonstrated the appearance of extra peaks in the leakage current as a result of an unwanted spin interacting with the double dot in the presence of spin orbit coupling 5 . An impurity tunnel-coupled to a single quantum dot in a silicon-germanium heterostructure has also been reported 6 , and this situation may also be relevant to other silicon devices which make use of dopants to confine spins 7,8 .…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…The current confirms the presence of appreciable spin orbit interaction (SOI) whose strength is controlled by the applied voltage to a gate electrode. Similar magneto-conductance measurements through a double dot formed in the channel of a silicon transistor device have demonstrated the appearance of extra peaks in the leakage current as a result of an unwanted spin interacting with the double dot in the presence of spin orbit coupling 5 . An impurity tunnel-coupled to a single quantum dot in a silicon-germanium heterostructure has also been reported 6 , and this situation may also be relevant to other silicon devices which make use of dopants to confine spins 7,8 .…”
Section: Introductionmentioning
confidence: 74%
“…One very well-known case is the presence of many nuclear spins, e.g., on the order of 10 4 − 10 5 , causing the host spins to decohere due to the Overhauser field 1,3 . However, experiments have demonstrated that even a single spin can affect the device operation 4,5 . For example, electrical transport measurements in a carbon nanotube double dot have revealed that an impurity spin attached to the nanotube modifies the expected leakage current in the spin blockade regime 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The metal-semiconductor interface will lead to electron gas (EG) at the interface having thickness similar to the spin diffusion length as shown in Figure 3 d. The charge potential in the EG gives rise to strong Rashba SOC, which is the underlying cause of SSE, thermal SGE and SOT observed in this study. The spin orbit coupling due to lack of inversion symmetry in Si metal-oxide semiconductor field effect transistor (MOSFET) has been reported using magneto-transport behavior in two-dimensional electron gas (2DEG) [47][48][49][50] and using spin resonance measurements 51 .…”
mentioning
confidence: 99%